Pinhole-free hole transport layers significantly improve the stability of MAPbI3-based perovskite solar cells under operating conditions1. Issue 30 (14th August 2015) - Ono, Luis K.; Raga, Sonia R.; Remeika, Mikas; Winchester, Andrew J.; Gabe, Atsushi; Qi, Yabing
<x xml:space="preserve">Abstract</x> A method has been developed to enable the deposition of pinhole-free spiro-MeOTAD hole transport layers (HTLs) on MAPbI3-perovskite films. Solar cells with pinhole-free HTLs show substantially improved stability under operating conditions.